A new rapid spectrophotometric method to determine the rosmarinic acid level in plant extracts - Ozturk, Mehmet; Duru, Mehmet E.; Ince, Burcu; Harmandar, Mansur; Topcu, GÜLAÇTI; TOPÇU, GÜLAÇTI (My University, 2010)
A novel spectrophotometric method to determine the amount of rosmarinic acid in unpurified methanol extracts of the plants was developed. Rosmarinic acid is a naturally occurring bioactive compound in plants as an ester of caffeic acid with 3,4-dihydroxyphenyl lactic acid. The developed method was based on the complexation of rosmarinic acid with Zr(4+) ions, giving a maximum absorbance at 362 nm. The absorptivity coefficient at this wavelength was found to be epsilon(362) = 2.66 x 10(4) L mol(-1) cm(-1). In fact, this method is also specified giving two more absorption bands in UV region at 299.5 and 263.5 nm besides 362 nm. In addition, the accuracy and sensitivity of the new developed method are compared with the direct UV and rosmarinic acid-Fe(2+) complex spectrophotometric methods by using methanol extracts of 11 Salvia species. As a conclusion, the present method is faster, cheaper, and more selective than the conventional methods for rosmarinic acid. (C) 2010 Elsevier Ltd. All rights reserved.